Radiolarites and silicified limestones sources used by Neolithic and Copper age societies in the Sava river basin (Croatia) - Šošić Klindžić, Rajna (2010)
In this poster a new research on possible sources of stone raw material during Neolithic in the region between Sava and Drava rivers was presented. Emphasis was given on the newly discovered sources and the possible major directions of people movements.